Redesigning: Handling Of Indonesian Election Violations Abroad To Realizing Quality 2024 Elections - Andi Intan Purnamasari; Sulbadana Sulbadana; Supriyadi Supriyadi; Aminuddin Kasim (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
Handling election violations abroad is one of the determinants of the quality of elections in Indonesia. With the rise of cases that occurred abroad during the 2019 general election, it is hoped that this will be a lesson to make an ideal design for handling election violations abroad in 2024. This research is executed differently from existing or previous research, for Example “The novelty of this research will make a significant contribution to determining the means, size, and function of the parliamentary threshold in the legislative election.” The conclusions of the research show that first, the urgency of handling election violations abroad to create order and peace, protect constitutional rights and uphold justice. Second, to realize the ideal design for handling election violations abroad in 2024, it is carried out increasing the number of members of the Overseas General Elections Supervisory committee from 3 to 5 people, making changes to Article 112 letter c, Article 507 of the Election Law, Article 13 paragraph (4) of the Regulation of General Elections Supervisory Agency Number 7 of 2018 and Article 60 paragraph (1) of the Regulation of General Elections Supervisory Agency Number 8 of 2018, and changing the paradigm of law enforcement from compliance level to internalization of legal Compliance in the 2024 elections.